Proposed Marketing Strategy for Products in a Niche Market (Case Study: 3Kurma) - Yolanda Gabrita Kamal (PT. Publikasiku Academic Solution, 2025)
Dates are widely consumed in Indonesia, especially during the Ramadan season. This study aims to identify innovative marketing strategies, understand date consumption patterns, and find obstacles that prevent dates from becoming a routine consumption option outside of Ramazan. The mixed-methods approach is employed, combining both quantitative and qualitative research methods to gain a comprehensive understanding of consumer behavior, motivation, and preferences related to date consumers. Data analysis was conducted using thematic analysis with the assistance of NVivo software to organize the data and identify key themes. The results from 235 respondents highlight key demographic and behavioral insights. Additionally, date type and quality are key factors in customer recommendations, indicating that sellers should balance traditional marketing with catering to younger generations by creating products aligned with healthy lifestyle trends and culinary innovation. 3Kurma can demonstrate the product's versatility and premium quality. Pop-up events at malls, markets, or popular local spots in Jakarta can be a highly effective marketing strategy to build brand awareness, create a sensory experience, and engage directly with their target audience in a unique and memorable way.